An Experimental Study on Electrical Behaviour of (Pb1-xSnx) TiO3(x=0.10,0.20,0.30) Ceramics - Subedi, Mitra Mani (Himalayan Physics, 2011)
(Pb1-xSnx)TiO3(x=0.10,0.20,0.30)(PST) powders are synthesized using the conventional dry route in a mixture of PbCO3,SnCl2.2H2O and TiO2.The samples are sintered at 1050°C to achieve about 95% of theoretical density. It is observed that PST sample reveals dielectric anomaly around 190°C for x=0.10,180°C for x=0.20 and no anomaly is observed for x=0.30 which confirms the ferroelectric behaviour of PST 10%,PST 20% and PST 30% as paraelectric. The peak value of the real part of dielectric constant is higher during cooling mode than that for heating mode as per simple Landau theory argument, which gives the thermal hysteresis of 10°C for PST 10%, 5°C for 20%.This observation confirms the first order nature of the ferroelectric to paraelectric transition and tending towards second order. The feature of PST has great applications such as capacitors, temperature sensors as well as humidity and gas sensors. So, it is recommended to extend further study. The Himalayan Physics Vol.2, No.2, May, 2011 Page: 54-56 Uploaded Date: 1 August, 2011